2021
DOI: 10.1002/jmrs.522
|View full text |Cite
|
Sign up to set email alerts
|

Imaging modalities for endoleak surveillance

Abstract: As the global population ages, the issue of abdominal aortic aneurysm continues to grow. With the evolution of new devices and refined operative technique, aneurysm treatment via endovascular aortic repair is becoming increasingly favourable. This, however, is not without drawbacks, where regular surveillance is paramount to long-term success and detection of post-procedure complications. Of these complications, endoleak is the most notable and poses the greatest risk of potential future aortic rupture. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…2,3 Complex aortic aneurysms with pathologies extending into the descending aorta might additionally require a thoracic/ fenestrated endovascular aortic repair combination (T/FEVAR). 5 Endoleaks are a common complication in endovascular aortic repair (EVAR) [6][7][8][9] and often result in re-intervention. 10 Therefore, such procedures require long-term surveillance to ensure patient safety.…”
Section: And Results In Lower Perioperativementioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Complex aortic aneurysms with pathologies extending into the descending aorta might additionally require a thoracic/ fenestrated endovascular aortic repair combination (T/FEVAR). 5 Endoleaks are a common complication in endovascular aortic repair (EVAR) [6][7][8][9] and often result in re-intervention. 10 Therefore, such procedures require long-term surveillance to ensure patient safety.…”
Section: And Results In Lower Perioperativementioning
confidence: 99%
“…[11][12][13] However, issues such as the cumulative radiation dose, contrast agent use in impaired renal function, limited differentiation of endoleak type as well as high costs are relevant limitations to consider for its use in clinical practice. 9,14,15 Subsequently, the use of other imaging modalities such as contrast-enhanced ultrasonography (CEUS) 14,16 or regular color duplex sonography (DUS) 17 have been investigated repeatedly for the follow-up of FEVAR procedures. Both techniques have already proven to be reliable in endoleak surveillance programs after EVAR.…”
Section: And Results In Lower Perioperativementioning
confidence: 99%
See 1 more Smart Citation
“…MR offers the advantages of no radiation exposure, less or no renal toxicity of contrast agents, and information about flow direction. Nevertheless, it has three main setbacks: classic MRI contraindications, magnetic susceptibility artifacts, and radiofrequency shielding effects [ 23 , 27 ]. Studies that have compared MR with CT imaging have demonstrated that MRI had a higher sensitivity to detect type II endoleaks.…”
Section: Discussionmentioning
confidence: 99%
“…der bildgebenden Modalität unterscheiden sich die Leitlinien: So wird bei den amerikanischen Guidelines der Ultraschall (US) mit Ausnahme der ersten Nachuntersuchung gleichwertig zur CTA gewertet, während die europäischen Leitlinien sogar den US vorrangig empfehlen, vor allem für die jährlichen Verlaufskontrollen, während die CTA nur bei den Kontrollen alle 5 Jahre zum Einsatz kommen soll. In diesem Bereich kann insbesondere der kontrastmittelverstärkte Ultraschall punkten, der bei deutlich niedrigeren Kosten eine höhere Sensitivität zur Detektion von Endoleaks als die CTA aufweist, insbesondere bei Typ-II-Endoleaks [ 18 , 22 , 50 , 56 ].…”
Section: Typ Vunclassified